Prarancangan Pabrik Alumunium Sulfat dari Asam Sulfat dan Kaolin Kapasitas 25.000 Ton/Tahun - Masrokan, Ahmad; , Ir. Haryanto AR., M.S; , Rois Fathoni, S.T. M.Sc. Ph.D (2016)
Alumunium sulphate factory aims to supply alumunium Suphate needs domestically. Alumunium sulphate Al2(SO4)3 known alum is one of the necessary chemicals for water treatment in waterworks and a variety of industry events, food an drinks. The process used for the formation of alumunium sulphate using heterogeneous phase reaction liquid and solid which produces a by product of Na2SO4, FeSO4 and Fe. Reaction process taking place in the reactor CSTR/RATB. The reacrion occurs at a temperature of 90 OC whith pressure 1 atm for 180 minutes with conversion in reaction of 85%, it is an exothermic reaction an direct running. Alumunium sulphate products are produced as much as 3.156,5656 kg/hour, to produce appropriate calculation then it takes as much sulfuric acid raw materials 4.747,003 kg/hour and kaolin as much as 1.646,9195 kg/hour. The supporting unit processes (utilities) include provision of water cooling 18.539,8128 kg/hour, water steam for the needs of 540,8879 kg/hour which in the production of diesel fuel with boilers of 79,014 Liter/hour, water for sanitation of 2.099,0872 kg/hour. Aluminium sulphate factory needs electricity of 406,610 kW provided from PLN and provided a generator set as a backup. Compressed air requirement of 30 m3/hour. This factory is planned to stand at karawang, West Java, by 2020 with the number of employess with 23.780 m2 as much as 158 people. Economic analysis of alumunium sulphate factory demonstrated against a profit before tax of Rp 90.900.115.811 per year after the cut profit reacher Rp 68.175.086.858. Return on Investment (ROI) before tax 38,77%, after tax 29,08%. Pay Out Time (POT) before tax 2,05 years dan after tax 2,56 years. Break even Point (BEP) of 47,78%, Shut Down Point (SDP) of 27,97% and Discounted Cash Flow (DCF) accounting of 43,17%. Feasibility analysisi of the data above, it was concluded that the factory is profitable and viable to set up.